Konsep Dasar Penataan Ruang dan Pengembangan Kawasan Perdesaan - Saefulhakim, H. R. Sunsun (Journal of Regional and City Planning, 1997)
Based on the Spatial Arrangement Act (UU No.24/1992) and, the author explores a definition of the rural areas in an integrated perspective spatial development. The rural areas is defined as an integral part of a region in which agriculture and natural resources management play as major activities. Thereby, the rural area plays important functional roles in: supplying tangible products such as food, energy, row materials for industries; maintaining the balance of water cycle, and temperature; controling air and soil pollution; and providing amenity resources. An urban biased market force often disregards these important functional roles of the rural area, thus leads to many environmental problems and social costs. The author pointed out the urgent needs to develop a spatial arrangement and regional development policy model emphasizing synergism among market forces, ecological sustainability, and social aspects. A silvofishery development is an example of the model that assure synergism between market forces and ecological sustainability. A participative partnership system of land management and agrotourism are pointed out as an example of the model that assure synergism between market forces, social concern, and ecological sustainability.PDF